Effects of maternal diabetes and fetal sex on human placenta mitochondrial biogenesis. (September 2017) - Jiang, Shaoning; Teague, April M.; Tryggestad, Jeanie B.; Aston, Christopher E.; Lyons, Timothy; Chernausek, Steven D.
Abstract: Abnormal placental function in maternal diabetes affects fetal health and can predispose offspring to metabolic diseases in later life. There are fetal sex-specific differences in placenta structure and gene expression, which may affect placental responses to maternal diabetes. The present study examined the effects of maternal diabetes on indices of mitochondrial biogenesis in placentae from male and female offspring. Mitochondrial DNA (mtDNA) copy number and expression of key regulators of mitochondrial biogenesis were assessed in placentae from 19 diabetic and 23 non-diabetic women. The abundance of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) and mitochondria transcription factor A (TFAM) were lower in female placentae compared to males, but not mtDNA content. In male offspring, maternal diabetes was associated with decreased placental PGC-1α and TFAM, and mitochondrial DNA (mtDNA) content. Male placental TFAM levels were highly correlated with PGC-1α and mtDNA content. However, despite decreased PGC-1α, concomitant changes in TFAM and mtDNA content by diabetes were not observed in females. In addition, TFAM abundance in female placentae was not correlated with PGC-1α or mtDNA content. In summary, placental PGC-1α/TFAM/mitochondrial biogenesis pathway is affected by maternal diabetes and offspring sex. Decreased PGC-1α in response to maternal diabetes plausibly contributes to impaired mitochondrial biogenesis in placentae of male offspring, which may affect long-term health and explain some of enhanced risk of future metabolic diseases in males. Graphical abstract: Highlights: Placental PGC-1α and TFAM proteins are lower in female offspring than males. Placental PGC-1α is reduced in both male and female offspring of diabetic women. The effects of maternal diabetes on TFAM/mtDNA content are fetal-sex dependent.